Berbagai genus bakteri pada eksoskeleton lalat di pasar tradisional: Kajian pustaka - Tomasowa, Revalina Caroline; Maulida, De Shila Syailinda; Pasaribu, Kezia Tio; Surtikanti, Hertien Koosbandiah (Public Health Risk Assesment Journal, 2024)
The existence of traditional markets is needed to fulfill the needs of life. However, the condition of traditional markets is less clean and even polluted so that it is inhabited by flies. Flies are animals that can become pathogenic agents and one of them is bacteria. The purpose of this study was to determine the various genus of bacteria in flies in traditional markets. The methods used were literature study and qualitative research. From the results of the review of several articles, it is known that there are three dominant fly species in traditional markets, namely Musca domestica, Sarcophaga haemorrhoidalis and Chrysomya megacephala. From the three fly species, seven genus of bacteria were found, namely Staphylococcus, Escherichia coli, Salmonella, Shigella, Vibrio, Providencia, and Serratia. Some of the bacteria originated from animal feces, meat, fish, polluted water infested by flies as pathogen-carrying agents. The fly species strongly suspected to be the most pathogen-carrying agent was Chrysomya megacephala as it was present in all markets. It can be concluded that in Traditional Markets there are three dominant fly species that carry seven genus of bacteria that can be identified and Chrysomya megacephala is the most pathogen-carrying agent.